The Public Health Impact of Parent-Reported Childhood Food Allergies in the United States - Gupta, Ruchi S; Warren, Christopher M; Smith, Bridget M; Blumenstock, Jesse A; Jiang, Jialing; Davis, Matthew M; Nadeau, Kari C (Pediatrics (Evanston), 2018)
: media-1vid110.1542/5840360268001PEDS-VA_2018-1235 BACKGROUND: Childhood food allergy (FA) is a life-threatening chronic condition that substantially impairs quality of life. This large, population-based survey estimates childhood FA prevalence and severity of all major allergenic foods. Detailed allergen-specific information was also collected regarding FA management and health care use. A survey was administered to US households between 2015 and 2016, obtaining parent-proxy responses for 38 408 children. Prevalence estimates were based on responses from NORC at the University of Chicago's nationally representative, probability-based AmeriSpeak Panel (51% completion rate), which were augmented by nonprobability-based responses via calibration weighting to increase precision. Prevalence was estimated via weighted proportions. Multiple logistic regression models were used to evaluate FA predictors. Overall, estimated current FA prevalence was 7.6% (95% confidence interval: 7.1%-8.1%) after excluding 4% of children whose parent-reported FA reaction history was inconsistent with immunoglobulin E-mediated FA. The most prevalent allergens were peanut (2.2%), milk (1.9%), shellfish (1.3%), and tree nut (1.2%). Among food-allergic children, 42.3% reported ≥1 severe FA and 39.9% reported multiple FA. Furthermore, 19.0% reported ≥1 FA-related emergency department visit in the previous year and 42.0% reported ≥1 lifetime FA-related emergency department visit, whereas 40.7% had a current epinephrine autoinjector prescription. Prevalence rates were higher among African American children and children with atopic comorbidities. FA is a major public health concern, affecting ∼8% of US children. However, >11% of children were perceived as food-allergic, suggesting that the perceived disease burden may be greater than previously acknowledged.